Heat and mass transfer effect on a radiative second grade MHD flow in a porous medium over a stretching sheet - Baitharu, A. P.; Sahoo, Sachidananda; Dash, G. C. (Journal of Naval Architecture and Marine Engineering, 2020)
A study on heat and mass transfer of a steady laminar boundary layer flow of an electrically conducting fluid of second grade in a porous medium subject to a uniform magnetic field past a semi-infinite stretching sheet with power law surface temperature or power law surface heat flux. The variations in fluid velocity, fluid temperature and species concentration are displayed graphically whereas the numerical values of skin friction, Nusselt number and Sherwood number are presented in tabular form for various values of the pertinent flow parameters. The asymptotic expansions of the solutions for large Prandtl number are also given for the two heating conditions. The temperature distribution decreases with the increase in thermal radiation parameter in case of PST and PHF. The rate of mass transfer at the solid surface increases in the presence of magnetic field and decreases with heavier diffusing species.